Perspectivas de pacientes com doença incurável sobre a morte clinicamente assistida: um estudo qualitativo e bioético - Almeida, Gabriela Franco de (2018)
This thesis, the result of a theoretical-argumentative and empirical-qualitative study, deals with the question of the vulnerability of patients diagnosed with an incurable and degenerative disease, as a problem for the choice of clinically assisted voluntary death. Considering, on the one hand, the informed and autonomous will of the person as a reason for the right to assisted suicide and voluntary euthanasia, and, on the other hand, human vulnerability, affecting the capacity to understand and decide rationally, as a strong reason against, we discuss, using the theoretical and empirical contributions of bioethics (conceptual aspects about vulnerability and capacity, factual and narrative aspects about the perspective of patients and their families, and aspects about some protocols in force), the pertinence of integrating clinically assisted suicide and voluntary euthanasia among the options for patient care under the above conditions. The work was divided into two methodological steps: 1) firstly, pertinent literature was consulted for conceptual clarification and data collection aiming the theoretical-argumentative discussion and 2) as a second step, a qualitative research of field was carried out, followed by analysis and evaluation of the data collected. Twelve participants with a diagnosis of incurable and degenerative disease were interviewed and the data were appreciated using Thematic Analysis. Through the first step it was possible to argue that, despite the fragility caused by illness, and under the assumption that the patient is not in major depression or with significantly impaired capacity of decision, then she should not be treated as vulnerable and unable to decide for his own death, or, alternatively, if she is considered vulnerable, she can still be considered potentially capable of deciding whether, after receiving due care to regain or strengthen its rational decision-making capacity, she decides to die with due clinical assistance, just as it happens in other similar contexts, especially in the refusal of treatments. Through the results of the second step, the themes found in the participants' responses show, predominantly and for most participants, agreement with clinically assisted death. When asked directly about assisted suicide and voluntary euthanasia, ten and nine participants, respectively, expressed themselves favorably. Religion and the negative representation of death appear as contrary arguments, as well as the negative interpretation of the physician's role in the case of voluntary euthanasia. On the other hand, the themes of autonomy, dignity, and respect for the suffering individual appeared in the justifications in favor of clinically assisted death. With the results of the qualitative research, together with the autonomy-based argument, it is advocated here to expand the possibilities of medical assistance in death cares, integrating both clinically assisted suicide and clinically assisted voluntary euthanasia among the options.